Some Remarks and Tests on the Dh1 Cryptosystem Based on Automata Compositions - Dömösi, Pál; Gáll, József; Horváth, Géza; Tihanyi, Norbert (Informatica, 2019)
In this paper we discuss NIST test results of a previously introduced cryptosystem based on automata compositions. We conclude that the requirements of NIST test are all fulfilled by the cryptosystem.